THE CONCEPT OF ISLAMIC SPIRITUAL HAPPINESS (a Review of Nasaruddin Umar’s Thought) - kerwanto kerwanto (TAWASUT, 2020)
This article is a review of a book written by Nasaruddin Umar, titled “Doors towards Happiness: Learning 9 Art of Happy Life in the World and the Hereafter/ Pintu-Pintu Menuju Kebahagiaan: Belajar 9 Seni Hidup Bahagia di Dunia dan Akhirat”. This study aims to photograph his unique ideas about Spiritual Happiness. Then, the author offers it as a theoretical review of Islamic Psychology, in response to the problem of happiness in Western-modern psychology. Through this study, the author showed Nasaruddin Umar's influence on the views of some Sufis such as Ibn ‘Arabi and ‘AbdulKarim al-Jillī in interpreting happiness. In addition, the author seeks to map several important principles used as the foundation of theory, both theoretical and practical.